2007
DOI: 10.5271/sjweh.1150
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of cancer risk among male and female shift workers

Abstract: Objectives Melatonin, a hormone that inhibits experimentally induced cancers, is suppressed by nighttime exposure to light so that nighttime shift workers may be at an increased risk of cancer. Previous studies of shift workers found an increased risk of breast cancer among women and suggested a possible increased risk of colon cancer among women and prostate cancer. The present study was conducted to see whether these previous findings could be confirmed and whether shift workers are at elevated risk for canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
155
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(167 citation statements)
references
References 29 publications
8
155
0
4
Order By: Relevance
“…In relation to melatonin, there have been several observational studies of night work, shift work or visual impairment, and sex hormone-related cancers such as prostate or breast (Feychting et al, 1998;Verkasalo et al, 1999;Kliukiene et al, 2001;Megdal et al, 2005;Kubo et al, 2006;Conlon et al, 2007;Schwartzbaum et al, 2007). However, there has been no study of sleep duration and prostate cancer risk, even though prostate cancer, like breast cancer, is also a sex hormone-related cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to melatonin, there have been several observational studies of night work, shift work or visual impairment, and sex hormone-related cancers such as prostate or breast (Feychting et al, 1998;Verkasalo et al, 1999;Kliukiene et al, 2001;Megdal et al, 2005;Kubo et al, 2006;Conlon et al, 2007;Schwartzbaum et al, 2007). However, there has been no study of sleep duration and prostate cancer risk, even though prostate cancer, like breast cancer, is also a sex hormone-related cancer.…”
mentioning
confidence: 99%
“…Pinheiro et al, 2006). Melatonin, which is secreted mainly from the pineal gland and plays a role in sleep duration, is suggested as one of the candidates responsible for the association in breast cancer (Brzezinski, 1997;Schernhammer and Schulmeister, 2004) as it influences the synthesis and secretion of sex hormones by promoting the release of gonadotropin-releasing hormone (Martin and Klein, 1976;Aleandri et al, 1996).In relation to melatonin, there have been several observational studies of night work, shift work or visual impairment, and sex hormone-related cancers such as prostate or breast (Feychting et al, 1998;Verkasalo et al, 1999;Kliukiene et al, 2001;Megdal et al, 2005;Kubo et al, 2006;Conlon et al, 2007;Schwartzbaum et al, 2007). However, there has been no study of sleep duration and prostate cancer risk, even though prostate cancer, like breast cancer, is also a sex hormone-related cancer.…”
mentioning
confidence: 99%
“…This is because melatonin suppresses the synthesis and secretion of sex hormones by promoting the release of gonadotropin-releasing hormone (Martin and Klein, 1976;Aleandri et al, 1996). In relation to melatonin secretion, there have been several observational studies on night work or visual impairment and breast cancer (Feychting et al, 1998;Verkasalo et al, 1999;Kliukiene et al, 2001;Schernhammer et al, 2001;Megdal et al, 2005;Pukkala et al, 2006;Schwartzbaum et al, 2007). In addition, there have been three prospective cohort studies of sleep duration and the risk of breast cancer, although with inconsistent findings (Verkasalo et al, 2005;Pinheiro et al, 2006;Wu et al, 2008).…”
mentioning
confidence: 99%
“…A cohort study of professional firefighters in Florida reported a 5-fold increased risk of cervical cancer, unadjusted for lifestyle habits [55]. A Swedish registry-based cohort study found a 39% non-significant increase in risk associated with shift work (SIR 1.39, 95% CI 0.82-2.19), however, the definition of shift work used in the study was very rough, including occupations in which at least 40% of the workers reported working rotating shifts (3 shifts per day), or workers who worked at least 1 night in the week preceding the interview [56]. A Finnish record-linkage study reported excess risks of cervical cancer of about 20 to 40% with exposures to aliphatic and alicyclic, aromatic, and chlorinated hydrocarbon solvents.…”
Section: Other Occupational Exposuresmentioning
confidence: 89%
“…A Swedish registrybased cohort study did not find increased risks associated with shift work, but the definition of shift work used in the study was very rough, including occupations in which at least 40% of the workers reported working rotating shifts (3 shifts per day), or workers who worked at least 1 night in the week preceding the interview [56]. A cohort study in the US reported an increased risk among nurses who worked at least 20 years in rotating shifts; the risk was larger in a subgroup of obese nurses, after adjustment for potential confounding factors (body mass index > 30 kg/m 2 ; RR 2.09, 95% CI 1.24-3.52), and increased with the duration of shift work [64].…”
Section: Endometrial Cancermentioning
confidence: 99%